Acrylamide Levels and Associated Health Risks in Traditional Arabic Coffee Roasts - Carmen M. Breitling-Utzmann; Steffen Schwarz; Dirk W. Lachenmeier (Proceedings)
This study examines the acrylamide levels in a range of roasted coffee samples from Bahrain, with a particular focus on traditionally very light roasted coffees. Acrylamide, classified as a Group 2A carcinogen by the International Agency for Research on Cancer (IARC), is formed during the roasting process as a byproduct of the reaction between amino acids and reducing sugars present in coffee beans. The acrylamide levels were quantified using the standard method EN 16618:2015, which employs liquid chromatography in combination with tandem mass spectrometry (LC-MS/MS). The results demonstrated that the acrylamide levels in very light-roasted coffee samples (646 µg/kg, n = 4), which exhibited characteristics similar to green coffee, were significantly above the European Union (EU) benchmark level for roasted coffee of 400 µg/kg. In contrast, medium-roasted coffee samples (154 µg/kg, n = 4) and dark-roasted coffee samples (62 µg/kg, n = 2) did not exceed the benchmark level. These findings indicate a potential health risk associated with the consumption of very light-roasted coffee, emphasizing the need for awareness and possible mitigation strategies to reduce acrylamide exposure in traditional Arabic coffee practices.